Mechanically-induced osteogenesis in the cortical bone of pre- to peripubertal stage and peri- to postpubertal stage mice - Plochocki Jeffrey H (Journal of Orthopaedic Surgery and Research, 2009)
Abstract Background Exercise during postnatal development plays a key role in determining adult bone mass and reducing the risk of fracture and osteoporosis later in life. However, the relationship between mechanically-induced osteogenesis and age is unclear. Elevated levels of estrogen during puberty may inhibit periosteal bone formation. Thus, magnitudes of mechanically-induced osteogenesis may be vary with pubertal state. Methods The present study uses a murine model to examine age-related changes in bone formation at the femoral midshaft with voluntary exercise. Pre- to peripubertal mice aged 3 weeks and peri- to postpubertal mice aged 7 weeks were randomly divided into sedentary and exercised groups and subjected to histomorphometric comparison after 4 weeks of treatment. Results Results of the experiment indicate that exercise significantly increased osteogenesis on the periosteal and endocortical surface of the mice in the older age group (P < 0.05). Exercise had no significant effect on bone formation of mice in the younger age group, although exercised mice exhibited more bone growth on average than controls. Endocortical apposition was the primary method of bone formation for all mice in the experiment; however exercised mice in the older age group were able to add more bone on the periosteal surface than age-matched controls and exercised mice in the younger age group (P < 0.05). Medullary area increased with age, but exercised mice in both age groups had smaller medullary cavities relative to overall bone area than controls. Conclusion These findings suggest that the amount and location of mechanically-induced osteogenesis differs by age during skeletal development. Late adolescence may be the optimal time to accrue bone mass and maximize bone strength.